2018
DOI: 10.1007/s00417-018-4149-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodialysis cleft repair and cataract management by phacoemulsification combined with internal tamponade using modified capsular tension ring insertion

Abstract: PurposeTo evaluate the surgical outcomes of cyclodialysis cleft repair and cataract management by phacoemulsification combined with internal tamponade using a modified capsular tension ring (MCTR) compared with direct cyclopexy.MethodsThe preoperative and postoperative characteristics of patients with cyclodialysis clefts who underwent surgery via insertion of an MCTR into the ciliary sulcus (MCTR group; 16 patients, 16 eyes) or direct cyclopexy (DC group; 16 patients, 16 eyes) were recorded.ResultsThe cyclodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Also, the rate of gas resorption and reattachment of the ciliary body may not exactly synchronise with each other (Chen et al. ). Again, these techniques can only be performed by posterior segment surgeons, thus needing a concerted effort by an anterior segment surgeon to diagnose and localise the cleft and the posterior segment surgeon to operate.…”
Section: Management Based On Current Evidence‐based Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Also, the rate of gas resorption and reattachment of the ciliary body may not exactly synchronise with each other (Chen et al. ). Again, these techniques can only be performed by posterior segment surgeons, thus needing a concerted effort by an anterior segment surgeon to diagnose and localise the cleft and the posterior segment surgeon to operate.…”
Section: Management Based On Current Evidence‐based Knowledgementioning
confidence: 99%
“…Chen et al. () compared endocyclotamponade and exocyclopexy and concluded that cleft closure occurred equally in both groups (62.5%), however, the former group had improved best‐corrected visual acuity. Also, five eyes of the exocyclopexy group required secondary intervention at a later date due to cataract progression, similar to that reported by Popovic et al.…”
Section: Management Based On Current Evidence‐based Knowledgementioning
confidence: 99%
“…Various non-surgical and surgical methods to close the cyclodialysis cleft and center the dislocated lens have been proposed [ 4 13 ]. Gupta et al [ 11 ] reported a case of cataract, zonular dialysis, cyclodialysis, and iridodialysis following blunt trauma that was successfully treated in a single procedure by placing two capsular tension rings (CTRs).…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al [ 11 ] reported a case of cataract, zonular dialysis, cyclodialysis, and iridodialysis following blunt trauma that was successfully treated in a single procedure by placing two capsular tension rings (CTRs). We previously performed phacoemulsification combined with an internal tamponade by insertion of a modified capsular tension ring (MCTR) into the ciliary sulcus to close cyclodialysis clefts and treat cataracts [ 12 , 13 ]. Appropriate positioning of a polymethyl methacrylate CTR or Cionni MCTR in the sulcus apposing the detached ciliary body against the sclera provides stable endocyclotamponade and endocyclopexy (in-out suture to aid fixation), which promotes cleft closure [ 8 , 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation